THE IMPACT OF SOCIAL WELFARE POLICIES ON SOCIAL DEVELOPMENT IN SOUTH AFRICA: AN NGO PERSPECTIVE - Lombard, A (Social Work/Maatskaplike Werk, 2007)
The democratic government of South Africa has adopted a developmental framework and is aspiring towards being a developmental state (Department of Social Development, 2006a:2). However, the aspiration to become a developmental state is being seriously questioned in view of the increasing gap between the rich and the poor over the country’s thirteen years of democracy. Although it was expected that it would take a considerable time to eradicate the legacy of the past (RSA, 2006:5) it is a matter of great concern that the levels of poverty and inequality are on the increase in South Africa. Although South Africa’s neo-liberal macro-economic policy contributed to an economic growth rate of 4,9% in 2006 (RSA, 2007a:5), the policy is criticised for not sufficiently achieving economic development. The social welfare sector is one area in which the macro-economic policy impacts on government’s responsibility for, and accountability to, the vulnerable and the marginalised in society.